Psychological Shyness and its Relationship to Learning Motivation in Long Jump Performance Among First Year Female Students in the College of Physical Education and Sports Sciences, Al-Muthanna University - Matrood , Maysaa; Sadeq , Ahmed (Journal of Physical Education, 2025)
The current research aims to develop a scale for psychological shyness and motivation to learn effectively through the long jump, and apply it to first-year female students in the College of Physical Education and Sports Sciences at al-muthana University. The aim is to identify the correlation between psychological shyness and motivation to learn effectively through the long jump.To achieve this goal, the researcher employed a descriptive approach, along with survey and correlational studies, as they are appropriate for the nature of the research problem.The research population comprised (52) first-year female students in the College of Physical Education and Sports Sciences at al-muthana University for the academic year (2024-2025).The researcher then developed a scale for psychological shyness based on a scale prepared by Salwa Abdul Mahdi Manhil, consisting of (24) items with three alternatives: (fully applicable, sometimes applicable, and not applicable at all). The total score on the scale ranged from (24-72). The researcher also developed a learning motivation scale based on the scale prepared by Muhammad Jabbar Muhammad Al-Shammari. The scale consists of (27) items with five alternatives: (agree to a great extent, agree to a great extent, agree to a medium extent, agree to a small extent, agree to a very small extent). The total score for the scale ranges from (27-135). The researcher then conducted a pilot study and extracted the scientific foundations for the questionnaires. The two questionnaires were then ready for application. The researcher began implementing the main experiment on Sunday, January 11, 2025. After administering the questionnaires, the researcher was able to obtain the results. She then used the statistical program (SPSS) to analyze the data and obtain the results. Based on this, she concluded that psychological shyness plays an important and effective role in learning motivation towards the long jump, as the results revealed significant correlations